Establishing a Training Program: Selected Experience (Relations industrielles / Industrial Relations, 1954)
The article reviews "Establishing a Training Program: Selected Experience," edited by Thomas Q. Gilson, William A. Holcombe and John D. Staley. Institute of Management and Labor Relations, Rutgers University, New Brunswick, N.J. (46 pages).